Examining the Perceptions and Challenges of Mathematics Homework Practice of Higher Secondary Teachers in Bhutan: A Mixed-Methods Study (American Journal of Multidisciplinary Research and Innovation, 2025)
Homework is an integral part of the Bhutanese education system; however, there is limited empirical evidence on its effectiveness at the higher secondary level. This study examines the perceptions and challenges associated with mathematics homework among higher secondary teachers in Bhutan using a convergent parallel mixed-methods design. Quantitative data were collected through an online survey involving 244 teachers from 83 higher secondary schools and 320 students from one school, selected using random sampling. Qualitative data were obtained through semi-structured interviews with 12 teachers. The findings indicate that both teachers and students hold positive perceptions of mathematics homework. However, teachers face several challenges, including assessing students’ homework, motivating them to complete it, and identifying authentic learners owing to students copying their homework. Student responses also shed light on the underlying causes of these challenges, such as the homework overload and homework control. The study highlights the need for improved homework practices to enhance the effectiveness of mathematics homework at the higher secondary level.